Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Pemahaman Konsep Matematika Siswa - Sri Wahyuni; Sri Hastuti Noer; Pentatito Gunowibowo (JURNAL PENDIDIKAN MATEMATIKA UNIVERSITAS LAMPUNG, 2013)
This is a quasi experimental research that aim to investigate the influence of problem based learning model for students mathematical conceptual understanding in 8th grade students SMPN 2 Way Seputih academic years 2012/2013.  The population of this research is all students 8th grade of SMPN 2 Way Seputih academic years 2012/2013 which are distributed in five class, whereas, the sample of this research  is two class which is taken by using purposive random sampling technique.  Based on hypothesis analysis, it is found a conclusion that problem based learning model has an influence for students mathematical conceptual understanding in 8th grade.Keywords: Problem Based Learning Model, Mathematic Concept Understanding